Dampak Penerapan Etika Periklanan Terhadap Efektivitas Iklan Layanan Masyarakat - Azli Shahaby; Satria Airlangga Setiawan; Daniel Handoko (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines the impact of advertising ethics on the effectiveness of public service advertisements. It aims to evaluate how adherence to ethical guidelines influences audience perception, trust, and behavioral responses. The research uses qualitative surveys to provide a comprehensive analysis. Findings indicate a significant positive correlation between ethical advertising practices and the effectiveness of public service campaigns, suggesting that ethical considerations are critical for successful public communication.